2020
DOI: 10.1007/s00526-020-01867-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity results for (p, q)-Laplacian equations with critical exponent in $${\mathbb {R}}^N$$ and negative energy

Abstract: We prove existence results in all of $${\mathbb {R}}^N$$ R N for an elliptic problem of (p, q)-Laplacian type involving a critical term, nonnegative weights and a positive parameter $$\lambda $$ λ . In particular, under suitable conditions on the exponents of the nonlinearity, we prove existence of infinitely many weak solutions with negative energy when $$\lambda $$ λ belongs to a certain interval. Our proofs use variational methods and the concentration compactness principle. Towards this aim we give a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…It is worth pointing out that [1, Theorem 1] actually asserted the existence of a sequence of solutions provided the L ∞ norm of K(x) := θb(x) is sufficiently small. However, we found that their argument can only produce a finite number of solutions in the same way as the statement of Theorem 1.3 and discussed it with the authors of [1] about this issue, please see Remark 4.4 for more details.…”
Section: Introduction and Main Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…It is worth pointing out that [1, Theorem 1] actually asserted the existence of a sequence of solutions provided the L ∞ norm of K(x) := θb(x) is sufficiently small. However, we found that their argument can only produce a finite number of solutions in the same way as the statement of Theorem 1.3 and discussed it with the authors of [1] about this issue, please see Remark 4.4 for more details.…”
Section: Introduction and Main Resultsmentioning
confidence: 71%
“…where 1 < q < s < p and the weight m is possibly sign-changing. We obtained the existence of nontrivial nonnegative solutions to [1] for a fixed λ and some range of parameter θ (depending on λ). In [1], Baldelli et al obtained the multiplicity of solutions for problem (1.2) when Ω = R N in a reverse way, that is, for θ fixed and small, they find some range of λ.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A key role in the proof of our results is the concentration compactness principles by Lions. For a detailed discussion on them, we refer to [5] and [6]. In particular, we are interested in the second concentration compactness principle, which regards a possible concentration only at finite points and where two different types (since we are in unbounded domains) of convergences are considered: the tight convergence of measures, whose symbol is * , and the "weak" convergence, denoted with .…”
Section: Preliminariesmentioning
confidence: 99%